Capital versus Revenue: Receipts, Expenditures, Profits and Losses in Accounting and Taxation - K.C., Jit Bahadur (NCC Journal, 2018)
Objective – This article aims to enlighten the theory of capital and revenue nature receipt and expenditure in accounting and taxation. Methodology/design/approach – Methodologically, this article adopts the descriptive research methods and qualitative approach based on the primary, secondary, and tertiary sources of information from Acts/laws, journals, reports, books, dictionary and encyclopaedia. Finding and conclusion – The study found that the income tax Act of Nepal does not define the terms capital and revenue receipt and expenditure clearly, but clarifies provisions of non-business taxation assets of the individual persons and net gains from business assets or liabilities for the entity and gains from depreciable assets for both persons. Thus, we argue that it should define to avoid vagueness in the law. A simple tax law increases both tax revenue and evasion while vague decreases both. Originality/value – This paper explicitly presents the state of capital and revenue receipt and expenditure in theory and practice. Thus, this paper furnishes facts about the stated subject and adds a new knowledge to the existing literature. NCC Journal Vol. 3, No. 1, 2018, Page: 71-81